PENENTUAN HARGA POKOK PRODUKSI DENGAN MENGGUNAKAN ACTIVITY BASED COSTING (ABC) DALAM RANGKA MENENTUKAN HARGA JUAL PADA UMKM AMPLANG BENGALON - Ervi Dwi Cahyati; Andi Syarifuddin; Naila Mundjichtuttazkiyyah (Sekolah Tinggi Ilmu Ekonomi Nusantara Sangatta, 2020)
The purpose of this study is to be able to provide input and sources of information about the benefits of applying the ABC method in determining the cost of production, so that it is expected that the company will be more effective and efficient in issuing its production costs and can be used as reference material, comparison, and additional knowledge that is expected to bring useful results. The research method is a quantitative descriptive analysis method. The results of the analysis of the discussion of this study, it can be concluded that the results of the study indicate that the calculation of the company's cost of production is lower than the calculation of the cost of production using the Abc method. This research is descriptive research